Pengaruh Kompetensi Dosen dan Kepuasan Kerja Dosen Terhadap Kinerja Dosen di Universitas KH A Wahab Hasbullah Tambakberas Jombang - Emi Lilawati; Fauziah Mashari (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2017)
There are several factors that can influence the performance of lecturer, namely lecturer competence and job satisfaction of lecturer. This study aims to determine: the influence of competence on the performance of lecturers; the influence of job satisfaction on lecturer performance; and the influence of competence and job satisfaction on lecturer’s performance. This research was conducted at The University of KH A Wahab Hasbullah Tambakberas Jombang. The number of samples in this study was determined by using Isac and Michael table with 5% level of sobriety and the technique used was nonprobability covience sampling, so the number of samples in this study was 99 respondents. The results of this study indicate that there is a positive correlation between the variables of lecturer competence, job satisfaction and lecturer performance.